Microbial Profiles and Risk Factors of Preexisting Biliary Infection in Patients with Therapeutic Endoscopy - Hua-Qiang Ruan; Guo-Lin Liao; Peng Peng; Shi-Quan Liu; Chang-Liang Wu; Jian-Fu Qin; Zhi-Hai Liang; Guo-Du Tang; Meng-Bin Qin; Jie-An Huang (Gastroenterology Research and Practice)
Background. The bile infection may already exist before the administration of an interventional procedure, despite no clinical manifestations of cholangitis detected. Blood cultures remained negative even in more than half of the febrile cases with cholangitis. Risk factors associated with bacterial growth in bile before the intervention are not well defined. To establish the bacterial profiles isolated from the bile samples and to identify risk factors for bacterial colonization in the bile system. Methods. Individuals who underwent endoscopic retrograde cholangiopancreatography (ERCP) interventions were enrolled. Bile samples were aspirated and were immediately transferred into a sterile tube for storage. Results. Positive bile cultures were detected in 363 (38.0%) of 956 patients, including 322 benign diseases and 41 malignances. Of 363 positive cases, 351 (96.7%) were monoinfection and 12 (3.3%) multi-infection. Escherichia coli were the most common Gram-negative bacteria (210, 56.0%), followed by Klebsiella pneumoniae (45, 12.0%). Enterococcus faecalis represented the most common Gram-positive microorganism (19, 5.07%), while Candida albicans (11, 2.93%) were the dominant fungi. Klebsiella pneumoniae were more frequently detected in malignant diseases (P=0.046). Age, previous ERCP history or OLT history, and CBD diameter were independent risk factors for positive cultures (P<0.05) while preoperative jaundice drug therapy was the protective factor for bile infection (P<0.05). Conclusion. Monomicrobial infection was dominant among all infections, and Klebsiella pneumoniae strains were more frequently isolated from patients with malignant diseases. To effectively manage patients who are at a high risk for bile infection, a detailed diagnosis and treatment plan for each case should be prepared.